Allozyme Based Genetic Variation between Hatchery and Natural Populations of Sahar (Tor putitora) - Wagle, Suresh K; Pradhan, Neeta; Gurung, Tek B; Bista, Jay D (Journal of Natural History Museum, 2015)
Sahar (Tor putitora) formed a substantial natural fishery in the major riverine and lacustrine ecosystem of Nepal. Biological diversity of this species is being threatened by various anthropogenic activities. In view of the conservational value and the aquaculture potential of T. putitora, significant development in artificial propagation of this species has been achieved. The successful hatchery production of T. putitora brought to the forefront problematic questions regarding genetic variation of the hatchery stocks. A study was, therefore, conducted to determine the genetic variability within and between hatchery stocks and their wild counterparts of T. putitora using allozyme markers. Analyses of seven enzyme systems resuled in 11 loci being resolved from lake population and two consecutive generations of hatchery populations of T. putitora. Based on five polymorphic loci, all populations had percentage polymorphic loci 45.45. Significant reduction (P<0.01) in number of alleles per locus was evident in hatchery populations (1.45 ±0.181) compared to lake population (1.72 ±0.90). Loss of rear alleles, EST-2*74, IDH*70 and GDH*33 occurred in both of the hatchery populations which were present in wild counterparts- the lake population. All populations under study conform to the Hardy-Weinberg equilibrium at the 1% level. Although not significant (P>0.05), observed heterozygosity increased in first generation of hatchery population (Ho= 0.181 ±0.233) compared to natural population (Ho=0.179±0.221). The Ho of second generation of hatchery population was lowest (0.119 ±0.143) among the populations studied. Loss of rare alleles from the two generations of hatchery population, while these alleles were present in corresponding natural populations suggested the founders (20-30 individuals) of the hatchery populations probably represented bottlenecks to very small effective population size (Ne). J. Nat. Hist. Mus. Vol. 26, 2012: 212-223